2020
DOI: 10.1016/j.chroma.2019.460433
|View full text |Cite
|
Sign up to set email alerts
|

Study of interactions between carboxylated core shell magnetic nanoparticles and polymyxin B by capillary electrophoresis with inductively coupled plasma mass spectrometry

Abstract: In this work, interactions of carboxylated core shell magnetic nanoparticles with polymyxin B sulfate were studied by connecting capillary electrophoresis with inductively coupled plasma mass spectrometry. The interaction was probed by affinity mode of capillary electrophoresis with 25 mM phosphate buffer at physiological pH. 54 Fe, 56 Fe, 57 Fe, 34 S, and 12 C isotopes were used to monitor the migration of an electroosmotic flow marker and the interaction of the nanoparticles with polymyxin B. The analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Their peak shapes and resolutions nevertheless are satisfactory for further characterization study. Compared to previously reported methods for CSMNPs detection [40,43], our CE-LEDIF method without LVSS allows an improvement of 3.5 times (compared to CE-MS) and 17 times (compared to CE-UV) respectively for the detection of the CSMNPs' magnetic cores. With the inclusion of the LVSS preconcentration step, a detection limit improvement of 340 was achieved compared to conventional CE-UV for this purpose.…”
Section: Lvss and Ce-ledif Of Csmnpsmentioning
confidence: 82%
See 1 more Smart Citation
“…Their peak shapes and resolutions nevertheless are satisfactory for further characterization study. Compared to previously reported methods for CSMNPs detection [40,43], our CE-LEDIF method without LVSS allows an improvement of 3.5 times (compared to CE-MS) and 17 times (compared to CE-UV) respectively for the detection of the CSMNPs' magnetic cores. With the inclusion of the LVSS preconcentration step, a detection limit improvement of 340 was achieved compared to conventional CE-UV for this purpose.…”
Section: Lvss and Ce-ledif Of Csmnpsmentioning
confidence: 82%
“…Herein, we report for the first time a CE coupled with light-emitting-diode (LED) induced fluorescence detection approach (CE-LEDIF) for CSMNPs, offering significant improvement of detection sensitivity compared to the previously reported methods using UV or inductively coupled plasma mass spectrometry (ICP-MS) detection [40][41][42][43]. This was achieved with a novel way to perform on-line electrokinetic preconcentration of CSMNPs via modulation of the EO mobility (µEO) in fused silica capillaries without recourse to any coating nor viscous gel.…”
Section: ) Introductionmentioning
confidence: 99%
“…Considering spectroscopic methods, few ultraviolet (UV) spectrophotometric [ 8–12 ] and just two fluorimetric publications [ 13,14 ] , one for each antibiotic, have been reported previously. Furthermore, several chromatographic techniques such as high performance liquid chromatography (HPLC), [ 15–23 ] liquid chromatography (LC), [ 24–33 ] thin layer chromatography (TLC), [ 10,34 ] ultrahigh performance liquid chromatography (UPLC) [ 35–37 ] , and electrophoretic techniques [ 38–41 ] have been published. Conversely, microbiological assays [ 42–44 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…techniques such as high performance liquid chromatography (HPLC), [15][16][17][18][19][20][21][22][23] liquid chromatography (LC), [24][25][26][27][28][29][30][31][32][33] thin layer chromatography (TLC), [10,34] ultrahigh performance liquid chromatography (UPLC) [35][36][37] , and electrophoretic techniques [38][39][40][41] have been published. Conversely, microbiological assays [42][43][44] have been reported.…”
mentioning
confidence: 99%
“…CE with a diode-array detector (DAD) was also utilized for monitoring interactions of Fe 3 O 4 NPs with bovine serum albumin [27]. In a recent report, CE-ICP-MS/MS was employed to study interactions between carboxylated core-shell magnetic nanoparticles and antibiotic (polymyxin B) in affinity capillary electrophoresis (ACE) mode, with the aim of developing a microdevice based on SPIONs to test bacterial resistance [28]. However, the experiments were conducted under one set of electrophoretic conditions only (no optimization trials reported) and were not directed towards quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%